Voorkeurstrategieë in die Noord-Sotho-vertaling van Terminologie van het tolken - Cornelius, Eleanor; Pienaar, Marné (Stellenbosch Papers in Linguistics Plus, 2018)
Cornelius and Pienaar (2017) point out that there is a need for standardised interpreting terminology in South Africa, not only in the indigenous languages, but also in English and Afrikaans. In order to bridge this gap and to contribute to the standardisation of interpreting terminology, these authors decided to translate the 2008 publication by Salaets, Segers and Bloemen, with the Dutch title Terminologie van het tolken, published by Vantitlt in Nijmegen, in Afrikaans and in English, and to provide translation equivalents of the terms in one Nguni (Zulu) and one Sotho language (Northern Sotho). The original Dutch was adapted accordingly. The title of this multilingual product is Interpreting terminology / Terminologie van het tolken / Tolkterminologie / Mareo a botoloki /Amatemu okutolika (Pienaar & Cornelius 2018).The first phase of the project is reported in Cornelius and Pienaar (2017), consisting of the following actions: (1) expanding the original lemma list to include interpreting terms with high frequency of use in South Africa, whilst at the same time also limiting the original lemma list to only those terms that are in use and relevant in a South African context, (2) translating the dictionary articles into Afrikaans and English, (3) localising the content for the South African user, including the additional comments and examples, and (4) adapting the original Dutch to reflect resulting localised content.In this article the focus is on the second phase of the project, namely the provision of translation equivalents in Zulu and Northern Sotho. Finding translation equivalents in Northern Sotho proved to be particularly difficult. In contrast to standardised languages such as English and Afrikaans, the lack of a Northern Sotho standard variety forced the translators who collaborated on the project to act mainly as terminologists, and not translators, as they were continuously confronted with problems relating to zero equivalence (lexical/linguistic gaps). Despite similarities and overlap, translation and terminology represent different knowledge domains. Problems translators grapple with can of course be terminological in nature, for instance when confronted with instances of lexical or linguistic gaps, where the target language lacks a translation equivalent for a source language term.Different approaches to terminography can be followed (Alberts 2017). In order to assist with the standardising of interpreting terminology, whilst also contributing to language development in Zulu and Northern Sotho, the traditional subject-oriented methodology was preferred in Interpreting terminology. This approach focuses on the concept, and the relationship between concepts and conceptual systems. Standardised terms and concepts enable effective communication and knowledge transfer in a particular domain. This approach typically involves eleven steps. In this article we demonstrate how the decision to include translation equivalents in Northern Sotho, in particular, resulted in some disruption of the steps and the order in which the steps were executed, and we highlight some of the stumbling blocks the Northern Sotho translators had to contend with. These translators resorted to a number of strategies to solve these problems, including generalisation, paraphrasing and borrowing.